Information Organization and Databases Foundations of Data Organization - Tanaka, Katsumi; Ghandeharizadeh, Shahram; Kambayashi, Yahiko (Springer US, 2000)
Information Organization and Databases: Foundations of Data Organization provides recent developments of information organization technologies that have become crucial not only for data mining applications and information visualization, but also for treatment of semistructured data, spatio-temporal data and multimedia data that are not necessarily stored in conventional DBMSs. Information Organization and Databases: Foundations of Data Organization presents: semistructured data addressing XML, query languages and integrity constraints, focusing on advanced technologies for organizing web data for effective retrieval; multimedia database organization emphasizing video data organization and data structures for similarity retrieval; technologies for data mining and data warehousing; index organization and efficient query processing issues; spatial data access and indexing; organizing and retrieval of WWW and hypermedia. Information Organization and Databases: Foundations of Data Organization is a resource for database practitioners, database researchers, designers and administrators of multimedia information systems, and graduate-level students in the area of information retrieval and/or databases wishing to keep abreast of advances in the information organization technologies
Keywords: Computer Science; Data Structures, Cryptology and Information Theory; Computer Science, general; Multimedia Information Systems; Information Storage and Retrieval; Computer science; Data structures (Computer science); Information storage and retrieval; Multimedia information systems